2015
DOI: 10.1186/s12885-015-1268-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of histologic subtype, p16INK4a expression, and presence of human papillomavirus DNA in penile squamous cell carcinoma

Abstract: BackgroundUp to 50% of penile squamous cell carcinomas (pSCC) develop in the context of high-risk human papillomavirus (HR-HPV) infection. Most of these tumours have been reported to show basaloid differentiation and overexpression of tumour suppressor protein p16INK4a. Whether HPV-triggered carcinogenesis in pSCC has an impact on tumour aggressiveness, however, is still subject to research.MethodsIn tissue specimens from 58 patients with surgically treated pSCC between 1995 and 2012, we performed p16INK4a imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 42 publications
3
39
1
4
Order By: Relevance
“…However, in contrast to these previous reports, we found a correlation between TERT-p mutation with favorable clinicopathologic parameters in penile SCC, including a low histologic grade, low mitotic count, absence of necrosis, and low MIB-1 index. These results are in line with the fact that TERT-p mutations were more frequently detected in non-HPV-related tumors, which are generally low-grade tumors with low mitotic activities [48]. Similarly, the tumors in non-HPV-related penile SCC tend to be larger than those in the HPV-related type, which may explain the correlation between TERT-p mutant type and larger tumor size.…”
Section: Discussionsupporting
confidence: 82%
“…However, in contrast to these previous reports, we found a correlation between TERT-p mutation with favorable clinicopathologic parameters in penile SCC, including a low histologic grade, low mitotic count, absence of necrosis, and low MIB-1 index. These results are in line with the fact that TERT-p mutations were more frequently detected in non-HPV-related tumors, which are generally low-grade tumors with low mitotic activities [48]. Similarly, the tumors in non-HPV-related penile SCC tend to be larger than those in the HPV-related type, which may explain the correlation between TERT-p mutant type and larger tumor size.…”
Section: Discussionsupporting
confidence: 82%
“…Several risk factors have been identified in PeCa etiology, including poor penile hygiene, phimosis and human papillomavirus (HPV) infection [4, 5]. A recent analysis of cancer registries showed that PeCa patient survival has not improved in Europe nor United States in the last 20 years [6].…”
Section: Introductionmentioning
confidence: 99%
“…Als entscheidender Nachteil der ISH in der Detektion von HPV-DNA wird die eingeschränkte Sensitivität angegeben [15]. Die Hochregulation des Tumorsuppressorproteins p16 INK4a (und der damit verbundene immunhistochemische Nachweis) wird als ein Versuch der Tumorabwehr gesehen, die mit der HPV-Infektion einhergehende unkontrollierte Zellproliferation zu unterbinden (u. a. durch Hemmung der onkogenen Transkription) [7,16]. Der immunhistochemische Nachweis von p16 INK4a wird demnach als Surrogatmarker für eine HPV-Infektion des Hochrisikotyps bei Patienten mit Peniskarzinom genutzt [7,10,16].…”
Section: Introductionunclassified
“…Die Hochregulation des Tumorsuppressorproteins p16 INK4a (und der damit verbundene immunhistochemische Nachweis) wird als ein Versuch der Tumorabwehr gesehen, die mit der HPV-Infektion einhergehende unkontrollierte Zellproliferation zu unterbinden (u. a. durch Hemmung der onkogenen Transkription) [7,16]. Der immunhistochemische Nachweis von p16 INK4a wird demnach als Surrogatmarker für eine HPV-Infektion des Hochrisikotyps bei Patienten mit Peniskarzinom genutzt [7,10,16]. Durch unsere Arbeitsgruppe wurde in einer früheren Arbeit für PSCC-Patienten mit p16 INK4a -Expression eine vergleichsweise geringere karzinomspezifische Mortalität (CSM) beschrieben; insgesamt sind die verfügbaren Daten hierzu jedoch inkonsistent [8 -11, 16].…”
Section: Introductionunclassified
See 1 more Smart Citation